Review of Modular Multilevel Converters Applied to High Voltage Ac and Dc Transmission Systems - Travieso-Torres, J; Diaz-Diaz, M; Uriarte-Gonzalez, M (Institute of Electrical and Electronics Engineers Inc., 2022)
Low-Frequency Alternating Current (LFAC) transmission systems have been recently proposed as an alternative to High Voltage Direct Current (HVDC) technology, mainly for offshore wind farms integration. Due to the high-power level required, Modular Multilevel Cascade Converters can be an appropriate alternative in these applications. However, most of the current research in MMCCs is focused on HVDC applications. Therefore, this paper reviews Hig Voltage Alternating Current, HVDC and LFAC transmission systems, comparing the potential application of the most studied AC-AC MMCC topologies in terms of component counts and appropriateness for LFAC transmission. © 2022 IEEE.